The Islamic State : an analysis of its origins and evolution - Lang, Mathilde (2015)
On 29th June 2014, the first day of the Islamic holy month of Ramadan, the Islamic State of Iraq and al-Sham's spokesman Abu Muhammad al-Adnani (ISIS) attracted the international community's attention by announcing the restoration of the Caliphate under the leadership of Abu Bakr al-Baghdadi, or Caliph Ibrahim. Adnani also announced that the organization would henceforth be named the Islamic State (IS), publicly displaying the group's international territorial ambitions. Since that declaration, literature has daily abounded on the subject. However, little remains known about the organization's history, purposes and identity. This dissertation is an analysis of IS' origins and evolution. Understanding IS is a necessary step in order to vanquish it. The main argument of this paper is that IS's recent swift rise has been facilitated by the confluence of four main exogenous factors: the Syrian civil war, the decline of Al Qaeda central, the US troops withdrawal from Iraq and the sectarian policies led by former Prime Minister Nouri al-Maliki. In other words, little credit should be given to IS itself; the group has only successfully exploited a number of external factors and has stepped into a breach opened and widened by a number of various actors.